"Butoh gives back the feeling to the people". Issue 3 (2nd July 2020) - Matchett, Sara; Mbasalaki, Phoebe Kisubi
Abstract: Our title is a quote from one of the sex workers. She is a member of the Sex Workers' Theatre Group (SWTG) who made this statement after intense sessions on butoh that lasted three hours each over a period of four days. The SWTG is part of a project that investigates gender and cultures of (in)equality, working with theatre and performance as the main methodological approach. Noting the health of sex workers, physical and emotional − in a legally and structurally constrained environment − is of particular concern, this research considers gendered inequalities through a holistic approach to wellbeing that recognises the specific demands of the contexts in which sex workers work. Working with butoh principals, a form of Japanese dance theatre whose techniques offer an embodied praxis, it draws on embodied cognition and how this manifest through emotion. Butoh techniques, which call for the body to move in non-conventional ways, speak to how the state of the body modifies the state of the mind and by extension, emotions, hence, our title. In this article, we ask two central questions: within the framework of wellbeing, in what ways does embodied cognition manifest when butoh techniques are applied with a group of sex workers, whose daily lived experiences are in the midst of violence – physical, emotional, judicial and structural? And secondly, in this specific context, could butoh offer strategies that work within the framework of wellbeing? With this framing, we would like to offer some insight into embodied cognitions that challenge gendered inequality and injustices with a group of sex workers in Cape Town.